2013
DOI: 10.1371/journal.pone.0060856
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Children with a Chronic Illness–Seasonal and Age-Related Variations in Serum 25-hydroxy Vitamin D Concentrations

Abstract: IntroductionChildren and adolescents with a chronic illness have potential risk factors for vitamin D deficiency. An optimal vitamin D status might have multiple health effects. This study evaluated vitamin D status and its association with age, gender, and season in a large cohort of chronically ill Finnish patients at a tertiary pediatric outpatient clinic. A cross-sectional register-based study was carried out, involving altogether 1351 children (51% boys, age range 0.2–18 years), who visited the outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 40 publications
14
27
1
Order By: Relevance
“…In line with the studies on healthy children and children with chronic illnesses, we found a significant negative correlation between 25(OH)D and PTH. However, our results contradict those of other studies, which found no relationship between 25(OH)D and PTH in cancer patients, but in healthy controls.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In line with the studies on healthy children and children with chronic illnesses, we found a significant negative correlation between 25(OH)D and PTH. However, our results contradict those of other studies, which found no relationship between 25(OH)D and PTH in cancer patients, but in healthy controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Meanwhile, in agreement with other studies, older age was associated with a reduced 25(OH)D level in our cohort. The prevalence of vitamin D inadequacy in preschool children was 23.3%, compared with 45.4% in school children.…”
Section: Discussionsupporting
confidence: 94%
“…We found that older age (>10 years) was significantly associated with both serum 25 (OH) D deficiency and reduced bone mass. These findings are similar to those described in children with chronic medical illness [36]. …”
Section: Discussionsupporting
confidence: 91%
“…Similarly, monitoring 25OHD concentrations as a public health policy for all individuals is impractical; fortunately, high-risk groups can easily be identified based on clinical profile ( table 2 ). [58] . Consensus guidelines for vitamin D supplementation have been drafted from a variety of pediatric/ endocrine groups [16,[59][60][61][62] .…”
Section: Evidencementioning
confidence: 99%
“…Children with chronic illnesses and conditions affecting vitamin D synthesis/absorption/metabolism may also benefit from supplementation and may require higher doses [58] but are not in the remit of this consensus on NR. …”
Section: Candidates For Preventative Vitamin D Supplementation Beyondmentioning
confidence: 99%